2013
DOI: 10.1597/12-234
|View full text |Cite
|
Sign up to set email alerts
|

Association between Interferon Regulatory Factor 6 Gene Polymorphisms and Nonsyndromic Cleft Lip with or without Cleft Palate in a Chinese Population

Abstract: Objective : To further confirm the association between two IRF6 single nucleotide polymorphisms and nonsyndromic cleft lip with or without cleft palate in a Chinese population. Participants : A total of 106 nonsyndromic cleft lip with or without cleft palate case trios and 129 control trios. Intervention : Two IRF6 single nucleotide polymorphisms, rs2235371 and rs642961, were genotyped for all case and control families. Case-control analysis and family-based linkage analysis were both performed for the two sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
3
8
1
Order By: Relevance
“…However, our research did not indicate any association between the transmission of rs2235375 and NSOFC. This agrees with a case-control study in a Mexican population where there was no significant difference between CL(P) cases and controls in the frequency of rs2235375 (P=0.08) [22]. Also a case-control triad study by Zhou et al [23], in a Chinese population, found no significant association between rs2235371 and CL(P) using FBAT analysis.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…However, our research did not indicate any association between the transmission of rs2235375 and NSOFC. This agrees with a case-control study in a Mexican population where there was no significant difference between CL(P) cases and controls in the frequency of rs2235375 (P=0.08) [22]. Also a case-control triad study by Zhou et al [23], in a Chinese population, found no significant association between rs2235371 and CL(P) using FBAT analysis.…”
Section: Discussionsupporting
confidence: 88%
“…However, the pregestational use of folic acid supplementation and presence of maternal IRF6 rs2235375 were found to be associated with NSOFC in the case-only study design. This finding was not supported by the Velázquez-AragĂłn et al [22] Mexican study. However, these differences may be related to differences in the study setting.…”
Section: Environmental Factors C* (%) a (%)contrasting
confidence: 60%
“…Therefore, the study demonstrated that VWS had significant phenotypic differences. Certain reports have confirmed that the IRF6 gene is one of the pathogenic genes for VWS (13,14). The present study demonstrated that IRF6 is important in jaw development and fusion.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the possible function of noncoding regulatory sequences, SNP rs642961 located within AP-2α DNA binding site in the upstream enhancer region (MCS-9.7) of the IRF6 gene has been identified and associated with CL/P in populations of European and Filipino origin (Rahimov et al, 2008). Similar analyses for this noncoding SNP of the IRF6 gene and NSCL/P susceptibility were confirmed in the Central European population (Birnbaum et al, 2009) and in the Chinese Han population (Pan et al, 2010; Zhou et al, 2013); however, analyses showed mixed susceptibility in the Brazilian population present in Brito et al (2012), but not in ParanaĂ­ba et al (2010) and de Souza et al (2016). No susceptibility was seen in a non-Hispanic white group study (Blanton et al, 2010), in a Swedish/ Finnish origin group study (Pegelow et al, 2014), or in Iran (Kerameddin et al, 2015).…”
Section: Discussionsupporting
confidence: 68%